PEMBERDAYAAN EKONOMI IBU RUMAH TANGGA DI DESA PURWODADI DALAM MELALUI EKONOMI KREATIF BEADS.IN - pratisti, cahyani; Wahyuningsih, Yusminar; Sutadipraja, Edwin; Rosananda, Shella (MALLOMO: Journal of Community Service, 2023)
The majority of housewives in Purwodadi Village, Tanjung Sari District, Lampung Province are craftsmen of tapis, knitting, wayang, and dancing costumes. The problem faced is that housewives only work when there are orders. Creative economic resources are needed through other handicrafts to earn additional income. Currently, the trend for bead creations is increasingly developing and is available in various marketplaces. Training in bead creation skills and how to market them is needed to increase the income of housewives so that they are more empowered. The method used is Participatory Rural Appraisal. After training, housewives can make beaded creations and market them through exhibitions and social media Instagram. After the training, there were 8 sales of tissue box creations and this provided additional income for housewives in Purwodadi Dalam Village. Other creative economic skills training is needed so that housewives in Purwodadi village become more skillful.